Aspectos biológicos e técnica de criação do gorgulho-da-goiaba, Conotrachelus psidii marshall (Coleoptera: Curculionidae) - Valente, Fabricio Iglesias [UNESP]; Benassi, Vera Lúcia Rodrigues Machado (Sociedade Brasileira de Fruticultura, 2014)
The species Conotrachelus psidii Marshall (Coleoptera: Curculionidae), considered a key pest of guava cultivation, is causing major damage in several producing countries of the fruit. The purpose of this study was to evaluate the biological parameters of the pest under controlled conditions, through the development of a rearing technique of pre-pupae and pupae that would allow daily observations. It was found that the substrate for an appropriate development of these phases was moistened clay soil (with survival rate of 78%). This soil type was used in the rearing method, which was developed to work in a climatic chamber at a constant temperature of 25 ± 1ºC, 12 h photoperiod and 70% RH ± 10%. The biological stages of the egg, larva, pre-pupa, pupa and egg-pupa lasted, on average, 4.25, 12.2, 106.6, 14.88, and 138.4 days, respectively. The adult stages in the soil, beginning of feeding, pre-oviposition, longevity, and post-oviposition lasted on average 22, 11, 51.9, 149.32, and 7.18 days, respectively. The average oviposition period lasted 120.27 days, with an average of 343.63 eggs per female. By the proposed rearing method, the development of pre-pupae, pupae and adults of the guava weevil could be daily monitored, without requiring the construction of a new chamber by the insects, thus reducing stress and input in terms of energy.

Considerada praga-chave da cultura da goiaba, Conotrachelus psidii Marshall (Coleoptera: Curculionidae) tem causado grandes prejuízos em vários países produtores desta fruta. A pesquisa objetivou avaliar os parâmetros biológicos da praga, sob condições controladas, através do desenvolvimento de uma técnica de criação que permitiu efetuar observações diárias de pré-pupas e pupas. Constatou-se que o substrato adequado para manutenção dessas fases foi o solo argiloso umedecido com viabilidade de 78%, sendo este o tipo de solo utilizado na técnica de criação, que foi desenvolvida para trabalhos em câmara climatizada, à temperatura constante de 25 ± 1º C, fotoperíodo de 12 horas e UR de 70% ± 10%. Quanto aos aspectos biológicos, a duração média do período de ovo, larva, pré-pupa, pupa e ovo-pupa foi de: 4,25; 12,2; 106,6; 14,88 e 138,4 dias, respectivamente. A duração média do período da fase adulta, no solo, início da alimentação, pré-oviposição, longevidade e pós-oviposição foi de, 22; 11; 51,9; 149,32 e 7,18 dias, respectivamente. O período médio de oviposição foi de 120,27 dias, com um número médio de 343,63 ovos por fêmea. A técnica de criação desenvolvida permitiu acompanhar diariamente o desenvolvimento de pré-pupas, pupas e adultos do gorgulho-da-goiaba, sem que eles necessitassem reconstruir nova câmara, mostrando ser menos estressante e onerosa do ponto de vista energético.
Biological aspects and technical rearing of guava weevil, Conotrachelus psidii marshall (Coleoptera: Curculionidae)
Keywords: Guava; biology; behavior; Goiabeira; biologia; comportamento